The Influence of Visual Appeal and Perceived Enjoyment on Brand Loyalty Through Customer Trust for Shopee Users in Yogyakarta - Adriana Winarti; Nonik Kusuma Ningrum; Bernadetta Diansepti Maharani (Journal La Sociale, 2023)
Facing increasingly fierce competition, one of the main strategies is to increase customer loyalty. Customers are the lifeblood of a business, because from customers a business gets income. Customer loyalty is the tendency for customer attitudes and behavior to favor one brand over another. Loyal ones will show an attitude of wanting to maintain relationships with service providers, such as a willingness to provide contact numbers, receive information/promotions, or provide recommendations. The population in this study were all students using Shopee in Yogyakarta. The sampling technique was purposive sampling with a sample size of 130 people. Data collection was carried out using questionnaires and data analysis in this research used Smart PLS. The influence of visual appeal, perceived enjoyment and customer trust is stated to be positive and significant because the original sample value obtained is positive and the p value is <0.05. The test results using the PLS approach produced a coefficient value for the influence of visual appeal on brand loyalty through customer trust with a value of 1.809 (p value 0.070 > 0.05), so it can be concluded that visual appeal has no effect on brand loyalty through customer trust. The test results using the PLS approach produced a coefficient value for the influence of perceived enjoyment on brand loyalty through customer trust with a value of 3.742 (p value 0.000 < 0.05), so it can be concluded that perceived enjoyment has a positive and significant effect on brand loyalty through customer trust.